The National School Feeding Program as a promoter of Food and Nutrition Education actions in Brazilian schools - Ottoni, IC (2019)
The National School Feeding Program - NSFP is the public health policy that guarantees the minimum supply of healthy food and offers space for the construction of healthy eating habits in Brazilian schools. The objective of the present study was to evaluate the presence of Food and Nutrition Education (FNE) actions within the framework of the NSFP to verify its adequacy toward the program's legislation and to investigate which parameters are predictors of running school gardens. This was a cross-sectional observational study using secondary data obtained from the database of the Efficient School Lunch Management Award for the year 2010, with a sample of 749 municipalities in Brazil. A binary logistic regression was performed, considering the running of school gardens as a dependent variable, and the FNE indicators and the demographic variables as independent. The model containing the presence of FNE in the school curriculum was significant (p<0.001). The presence of FNE in school curricula OR=2.406;95%CI=[1.725, 3.357] was the most significant predictor of running school gardens, followed by the use of food from family farms OR=2.049;95%CI=[1.477, 2.842] and the carrying out of culinary workshops OR=2.032;95%CI=[1.442; 2.863], considering p<0.05. The presence of FNE in the school curriculum was positively associated with growing vegetable gardens, showing that complex actions that require more resources can be stimulated from simpler measures, and the NSFP as a public health policy is an important tool to promote actions throughout the national territory.